INFLUENCE OF THE EMISSIONS OF COAL INDUSTRY ENTERPRISES ON PUBLIC HEALTH - Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Олещенко, Анатолий Михайлович (Medicine in Kuzbass, 2017)
Subject. The emissions of coal industry enterprises in Novokuznetsk. Objective. Assessment of ecological risk to the public health from the emissions of coal industry enterprises in Novokuznetsk. Methods. Estimation of the enterprise emissions was carried out on the basis of the analysis of the volumes of maximum permissible emissions (MPE). The hazard indexes for acute and chronic exposure were determined. We calculated the maximum and average annual concentrations of toxic substances from each emission source at each point of exposure to concentrations (PEC) of toxic substances associated with the microdistricts of residential area based on the distance between each PEC and each emission source, and the risks to the public health were calculated. Main results. Based on the results of the risk assessment, conclusions regarding the impact of the emissions of the enterprise of coal mining and enrichment on the health of the population of Novokuznetsk were drawn and their contribution to the reduction of the health level of the residents was assessed. Conclusions. On the whole, the emissions of coal industry enterprises of the city do not have a significant impact on the public health.